2022
DOI: 10.1111/pce.14400
|View full text |Cite
|
Sign up to set email alerts
|

Plants acclimate to Photosystem I photoinhibition by readjusting the photosynthetic machinery

Abstract: Photosynthetic light reactions require strict regulation under dynamic environmental conditions. Still, depending on environmental constraints, photoinhibition of Photosystem (PSII) or PSI occurs frequently. Repair of photodamaged PSI, in sharp contrast to that of PSII, is extremely slow and leads to a functional imbalance between the photosystems. Slow PSI recovery prompted us to take advantage of the PSI-specific photoinhibition treatment and investigate whether the imbalance between functional PSII and PSI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…To gain further insight into the regulation of photosynthetic energy balance on the protein level, we investigated changes in thylakoid protein abundances in plants grown under FL conditions, as short‐term light changes typically do not lead to major adjustments of photosynthetic protein contents (Kono & Terashima, 2014 ; Schöttler & Tóth, 2014 ) in contrast to long‐term acclimation (Flannery et al, 2021 ; Niedermaier et al, 2020 ). Short‐term changes in protein abundance of photosystems were especially not expected, due to the rapid repair of damaged PSII centers via D1 protein turnover (Aro et al, 1993 ; Järvi et al, 2015 ) and high stability of PSI reaction center proteins without repair, despite severe PSI photoinhibition (Kudoh & Sonoike, 2002 ; Lempiäinen et al, 2022 ; Tiwari et al, 2016 ; Zhang & Scheller, 2004 ). In kvc , the long‐term growth in FL conditions revealed a decrease in PSI (PsaB), ATP synthase (AtpF), and only a minor decrease in PSII (D1 and CP47) protein contents, whereas Cytbf (PetA), LHCII (LHCB2), and ZE contents remained similar, and PSBS together with VDE increased in comparison with WT (Figure S7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To gain further insight into the regulation of photosynthetic energy balance on the protein level, we investigated changes in thylakoid protein abundances in plants grown under FL conditions, as short‐term light changes typically do not lead to major adjustments of photosynthetic protein contents (Kono & Terashima, 2014 ; Schöttler & Tóth, 2014 ) in contrast to long‐term acclimation (Flannery et al, 2021 ; Niedermaier et al, 2020 ). Short‐term changes in protein abundance of photosystems were especially not expected, due to the rapid repair of damaged PSII centers via D1 protein turnover (Aro et al, 1993 ; Järvi et al, 2015 ) and high stability of PSI reaction center proteins without repair, despite severe PSI photoinhibition (Kudoh & Sonoike, 2002 ; Lempiäinen et al, 2022 ; Tiwari et al, 2016 ; Zhang & Scheller, 2004 ). In kvc , the long‐term growth in FL conditions revealed a decrease in PSI (PsaB), ATP synthase (AtpF), and only a minor decrease in PSII (D1 and CP47) protein contents, whereas Cytbf (PetA), LHCII (LHCB2), and ZE contents remained similar, and PSBS together with VDE increased in comparison with WT (Figure S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…photosynthetic protein contentsSchöttler & T oth, 2014) in contrast to long-term acclimation(Flannery et al, 2021;Niedermaier et al, 2020). Short-term changes in protein abundance of photosystems were especially not expected, due to the rapid repair of damaged PSII centers via D1 protein turnover(Aro et al, 1993;Järvi et al, 2015) and high stability of PSI reaction center proteins without repair, despite severe PSI photoinhibition(Kudoh & Sonoike, 2002;Lempiäinen et al, 2022;Tiwari et al, 2016;Zhang & Scheller, 2004). In kvc, the long-term growth in FL conditions revealed a decrease in PSI (PsaB), ATP synthase (AtpF), and only a minor decrease in PSII (D1 and CP47) protein contents, whereas Cytbf…”
mentioning
confidence: 99%
“…Therefore, it is possible that PSI redox state is an overlooked factor in the signalling pathway for the LTR. Indeed, there is evidence that the redox state of the Trx/Fd system, which is reduced via electrons from PSI, is a key factor in shaping the LTR (Ibrahim et al., 2022 ; Lempiäinen et al., 2022 ), an idea which requires further investigation. The differences between the mutants and WT were largely abolished by growth in HL, which is consistent with the primary role of the STN7/TAP38 system in LL.…”
Section: Discussionmentioning
confidence: 99%
“…PSI is not totally resistant to excess excitation, and it may be further protected by modifying or eliminating subunits that are responsible for LHCII binding [50]. Recently, it was demonstrated that PSI is quite sensitive to fluctuating light intensities [51]. In addition, the formation of a stable PSI-PSII megacomplex in rice results in energy spillover [52].…”
Section: Second-to-minute Coupling and Slipsmentioning
confidence: 99%